1994
DOI: 10.1063/1.466633
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of high pressure gas on the rotator phases of normal alkanes

Abstract: The effects of high pressure gases (P≤400 bar) on the RII, RI, and RV rotator phases of 21, 23, and 25 carbon normal alkanes were studied via x-ray scattering. We have measured the pressure and temperature dependence of the rotator structures and present these results in terms of the essential structural parameters: layer spacing, area per molecule, lattice distortion, and tilt. The pressure was generated by one of three gases: helium, nitrogen, or argon. In the rotator phases, argon and nitrogen intercalate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 44 publications
6
60
0
Order By: Relevance
“…The lifetime above ≈ 600 MPa is almost constant. It is known from infrared studies that up to pressures of 10 GPa no phase transitions are found due to the close-packed nature of the rigid phase [8]. The intensity I 3 in the whole range of the rigid phase in nonadecane is pressure independent.…”
Section: Pressure Induced Phase Transitionsmentioning
confidence: 80%
See 1 more Smart Citation
“…The lifetime above ≈ 600 MPa is almost constant. It is known from infrared studies that up to pressures of 10 GPa no phase transitions are found due to the close-packed nature of the rigid phase [8]. The intensity I 3 in the whole range of the rigid phase in nonadecane is pressure independent.…”
Section: Pressure Induced Phase Transitionsmentioning
confidence: 80%
“…To this class belong some biomolecules, but linear negative compressibility was also found in the rotator phase of n-alkanes and their derivatives [8]. The PALS method detects the changes of free volume, not the bulk properties of solid, thus the positron studies can supply additional information about this counterintuitive property.…”
Section: Gas Induced Free Volume Swellingmentioning
confidence: 99%
“…It can be due to close packed structure of lamellae; Sirota et al (1994) report that no further phase transitions are observed up to 10 GPa. If our supposition (Goworek et al, 2003) that Ps locates in the gaps between the lamellae is valid, the existence of Ps at very high pressure can be explained by very low compressibility of alkane crystal in the direction perpendicular to the lamella surface (by two orders of magnitude less than along the lamella).…”
Section: Article In Pressmentioning
confidence: 91%
“…The 360 w X lower solid-solid transition could only " " be observed up to 20 MPa. Only few f other high-pressure studies of tbis kind are reporte in literature [19,20]. In this pompa context we note the usefulness of pVT measurements [4,[26][27][28].…”
Section: Ritimentioning
confidence: 99%
“…This fact strongly indicates that the molecules jump out from the layer surface by the thermal motion. High pressure phase diagrams420 have been established for n-alkanes [14,15,[17][18][19][20][21][22] and polymers [23][24][25]. Josefiak et al performe DT A measurements under pressure for some nalkanes in the range C27 to C38 [14].…”
Section: Ritimentioning
confidence: 99%